2017
DOI: 10.1136/gutjnl-2016-312162
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of primary human hepatocytes and prevention of hepatitis B virus reinfection efficiently deplete nuclear cccDNA in vivo

Abstract: We demonstrate that human hepatocyte division even without involvement of cytolytic mechanisms triggers substantial cccDNA loss. This process may be fundamental to resolve self-limiting acute infection and should be considered in future therapeutic interventions along with entry inhibition strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
173
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(188 citation statements)
references
References 53 publications
9
173
4
2
Order By: Relevance
“…In line with our previous study,27 the greatest expansion of human hepatocytes (qRT-PCR of human beta-globin DNA) is observed within the first 4 weeks and in particular in the first 2 weeks post-transplantation (figure 5A). During this proliferation period, HBV viraemia rapidly dropped (figure 5B) and accordingly, intrahepatic HBV markers strongly decreased (eg, pregenomic HBV RNA (pgRNA) and HBV DNA per cell, see online  supplementary figure 2) or were below the detection limit (circulating HBsAg and cccDNA per cell).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In line with our previous study,27 the greatest expansion of human hepatocytes (qRT-PCR of human beta-globin DNA) is observed within the first 4 weeks and in particular in the first 2 weeks post-transplantation (figure 5A). During this proliferation period, HBV viraemia rapidly dropped (figure 5B) and accordingly, intrahepatic HBV markers strongly decreased (eg, pregenomic HBV RNA (pgRNA) and HBV DNA per cell, see online  supplementary figure 2) or were below the detection limit (circulating HBsAg and cccDNA per cell).…”
Section: Resultssupporting
confidence: 92%
“…This experimental setting enables infected human hepatocytes to proliferate within the regenerating liver of young mice for around 8 weeks post-transplantation. As recently shown,27 in vivo proliferation of HBV-infected human hepatocytes caused a rapid drop of all serological and intrahepatic HBV markers, including cccDNA. Here, we show that although only one-third of human hepatocytes were HDAg positive 3 days post-transplantation, HDV RNAs and HDAg-positive cells were still detected at later time points during cell proliferation and appeared to form clusters of HDAg-positive human hepatocytes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Here, the study by Allweiss et al in this issue11 comes in, taking advantage of a sophisticated in vivo HBV infection model based on human liver chimeric urokinase-type plasminogen activator (uPA)/severe combined immunodeficiency (SCID)/beige (USB) mice 12. Overexpressed uPA damages the mouse hepatocytes, allowing partial liver reconstitution by primary human hepatocytes (PHH); the SCID/beige immunodeficiency, comprising a lack of functional B and T cells and natural killer cell functions, prevents xenograft rejection—and in the current study simplified the complex multifactorial impacts on cccDNA levels.…”
mentioning
confidence: 85%
“…It is tempting to speculate that distinct populations of cccDNA will differ in their susceptibility to degradation potentially also during cell division. We recently showed that in vivo proliferation of HBV-infected primary human hepatocytes leads to a strong cccDNA reduction in the liver of human chimeric mice [75]. Remarkably, cell division appeared to cause not only cccDNA dilution among daughter cells but also intrahepatic cccDNA loss.…”
Section: The Contribution Of Cell Division To Hbv Resolutionmentioning
confidence: 99%